Income inequality, banking competition, and monetary policy. - Ghossoub, Edgar A.; Reed, Robert R. (Southern Economic Journal, 2025)
Previous research has shown that inflation contributes to income inequality. However, in recent years, there have also been increasing concerns about the effects of concentration in the banking system on economic activity. Notably, we ask the fundamental questions: "How does the concentration of assets in the banking system contribute to the concentration of income in society? Do the effects of inflation on inequality depend on the degree of banking concentration?" We develop a general equilibrium model with heterogeneous agents and microeconomic foundations for financial intermediaries to study the effects of concentration and monetary policy. The model predicts that concentrated banks contribute to inequality by holding large amounts of liquid assets in order to raise private—but not social—returns from capital investment. As concentrated banks distort the level of investment in the economy, the adverse effects of inflation on inequality are magnified in concentrated banking systems.